Relationship between Biblical Context and Fulfillment of Mission among Akurinu Believers in Nairobi County, Kenya. - Nderitu Wambugu, Simon; Kibor, Esther; Koros, William (Editon Consortium Journal of Arts, Humanities and Social Studies (ECJAHSS), 2019)
The intent of this study was to look into the relationship between biblical context and fulfilment of mission among the Akurinu believers in Nairobi County, Kenya. Two theories that guided the study were Divine Command Theory (DCT) and Diffusion of Innovations Theory (DIT). Descriptive research design under mixed methods research was adopted. Akurinu congregations registered with the General Conference of Akurinu Churches Assembly (GeCACA) in Nairobi County were sampled using simple random, proportionate and purposive techniques to obtain 336 Akurinu believers and 18 leaders respectively out of a population of 2,600 congregants. Structured and semi-structured questionnaires and interview guides were used to collect data. Validity and reliability were ensured through piloting and expert advice. Software Package for Social Sciences (SPSS), version 22.0, was used to generate multivariate linear regression models at alpha=0.05. Frequency tables, themes and inferential statistics were used to present data. SPSS output with an r-value of 0.207 indicated that there was a weak positive relationship between biblical context and fulfilment of the mission. An alternative hypothesis was accepted. The findings were useful to Akurinu leaders, believers, researchers and policymakers among GeCACA national leadership towards biblical contextualisation of theology.
Keywords: Biblical hermeneutics; contextual theology; contextualisation; diffusion; divine commands